2019
DOI: 10.1538/expanim.18-0089
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin protects rat carotid artery from balloon injury and activates the NRF2 antioxidant pathway

Abstract: Percutaneous coronary intervention (PCI) is main treatment for acute coronary syndrome (ACS). However, restenosis caused by PCI-induced injury influences the outcome of patients. Linagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, has been reported to ameliorate intimal hyperplasia post vascular injury. The underlying mechanisms by which linagliptin protects against balloon injury are unclear and require to be explored. Herein, Wistar rats with carotid artery balloon injury were given 1, 2 or 3 mg/kg/day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Nrf2 is known to stimulate the heme oxygenase-1 (HO-1) axis, which is a potent anti-inflammatory target [ 44 ]. It has been reported that DPP-4 inhibitors activate the Nrf2/HO-1 pathway [ 45 , 46 , 47 ]. In addition, Nrf2/Kelch-like ECH-associated protein1 (Keap1) signaling pathways play an important role in preventing oxidative stress [ 48 ].…”
Section: Mechanisms Underlying Renoprotection By Dpp-4 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nrf2 is known to stimulate the heme oxygenase-1 (HO-1) axis, which is a potent anti-inflammatory target [ 44 ]. It has been reported that DPP-4 inhibitors activate the Nrf2/HO-1 pathway [ 45 , 46 , 47 ]. In addition, Nrf2/Kelch-like ECH-associated protein1 (Keap1) signaling pathways play an important role in preventing oxidative stress [ 48 ].…”
Section: Mechanisms Underlying Renoprotection By Dpp-4 Inhibitorsmentioning
confidence: 99%
“…BNP is clinically used for the diagnosis and evaluation of CVD [ 69 ]. BNP is synthesized as a 134-amino acid precursor (prepro BNP) that is processed to proBNP [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , …”
Section: Dpp-4 Substratesmentioning
confidence: 99%
“…In a rat IA model with ligation of carotid and renal arteries, EPO increased circulating EPCs, reduced the formation and progression of IAs, and reduced the expression of inducible nitric oxide synthase (iNOS) and MMPs [ 85 ]. Dipeptidyl peptidase-4 (DPP-4) inhibitors including sitagliptin have been shown to have beneficial effects in alleviating vascular remodeling and cardiac infarction by reducing ROS via the Nrf2/HO-1 pathway [ 86 , 87 ]. Consistent with this notion, the DPP-4 inhibitor anagliptin inhibited the accumulation of macrophages in IAs and prevented IA growth.…”
Section: Ho-1 In Intracranial Aneurysmmentioning
confidence: 99%
“…Carotid artery balloon injury model was constructed as previous reported. 21 Briefly, the male Wistar rats were anaesthetized (3 vol %) with isoflurane by inhalation. Then, the common carotid artery of left side was exposed.…”
Section: Carotid Artery Balloon Injury Modelmentioning
confidence: 99%